Avaliação da capacidade de fixação de fósforo pelo solo - Catani, R. A.; Pellegrino, D. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1960)
Phosphate "fixation" is the convertion of soluble into insoluble phosphate in the soil. There are many factors conditioning phosphate fixation by soil such as reactions originating less soluble compounds (phosphates of iron, aluminum, calcium, magnesium, etc.), PO4-3 adsorption by the colloidal fraction of soils, PO4-3 absorption by the soil microflora, etc. Certain soils of the state of São Paulo (Brazil) are relatively rich in both iron and aluminum oxides. PO4-3 fixation, using P31 and P32 has been verified by researchers, specially with "Terra Roxa". The known methods for fixation evaluation are conventional as this depends on phosphate solution concentration, pH, time of contact between soil and solution, relation of sample weight to solution volume, shaking time, etc. In this experiment, the following conventional method was used: 4 g of soil were shaken for 15 minutes at 30-40 rpm, in 300 ml Erlenmeyer flask in a Wagner shaking machine, together with 100 ml of 0,03 normal phosphate solution (being 0,01 normal as PO4-3 contributed by H8PO4 and 0,02 normal as PO4-3 from KH2PO4). After shaking it was set aside for 24 hours and then filtered. Phosphate was determined in a suitable aliquot of both the original solution (blank) and the soil extract, by the vanadomolibidic-phosphoric acid method. From phosphate concentration in the blank minus phosphate concentration in the soil stract the rate of fixation by 100 g of soil was calculated. The data obtained show that "Terra Roxa" and "Terra Roxa Misturada" have a fairly high PO4-3 fixation capacity, varying from 10 to 24 milliequivalents of PO4-3 per 100 g of soil.